Increasing Basic Reading Skill for Children with Learning Difficulties through SILABA Method - Fatmawati Fatmawati; Marlina Marlina (Department of Special Education, 2021)
This research is motivated by the problems found in five students with learning difficulties in grade two. This study aims to prove the effectiveness of the SILABA method in improving beginning reading skills for children with learning difficulties. This study used an experimental method in the form of a pre-experimental design or a quasi-experimental with the type of one-group pretest-posttest design. This research conducted pre-test, treatment, and post-test. The treatment was given with the SILABA method and continued by giving a post-test to see the ability after treatment. The pre-test and post-test values were processed and compared using the Mann-Whitney to test the research hypothesis. The results of this study were obtained based on data analysis seen from the pre-test value. The data was processed using the Mann-Whitney test. It was obtained that Uhit = 2.5 and Utab = 2 with n = 5 at a significant level of 95% and = 0.05. The alternative hypothesis is accepted because Uhit > Utab, so it is proven that the SILABA method is effectively used to improve early reading skills for children with learning difficulties. Suggestions in this study are expected that schools can develop students’ initial reading skills using the SILABA.